Application of response surface methodology for optimization of lead removal from an aqueous solution by a novel superparamagnetic nanocomposite. Issue 1 (March 2017) - Javanbakht, Vahid; Ghoreishi, Seyyed Mohammad
The present study focuses on the response surface methodology (RSM) for the optimization of lead removal from an aqueous solution by a novel superparamagnetic nanocomposite. A rotatable central composite design and the response surface methodology were used to conduct and to analyze the experiments, respectively. The adsorption process was investigated as a function of the four factors consisting of pH (4.0–6.0), temperature (20℃–60℃), initial lead concentration (10–90 mg/L) and adsorbent dosage (0.2–1.0 g/L). The maximum lead adsorption capacity was obtained to be 124.955 mg/g under the optimal conditions of 5.49, 60℃, 89.08 mg/L, and 0.48 g/L for the solution pH, temperature, initial lead ion concentration, and the adsorbent dosage, respectively. The desirability function was used to find an optimum point where the desired conditions could be obtained. The superparamagnetic nanocomposite could be used as an adsorbent for the removal of toxic heavy metals from water and wastewater.